2015
DOI: 10.1124/dmd.115.067439
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Phenobarbital on Expression of UDP-Glucuronosyltransferase 1a6 and 1a7 in Rat Brain

Abstract: UDP-glucuronosyltransferase (UGT), a phase II drug-metabolizing enzyme, is expressed in the brain and can catalyze glucuronidation of endogenous and exogenous substrates in the brain. Thus, changes in UGT1A expression could affect homeostasis and drug efficacy. Phenobarbital (PB), a typical inducer of drug-metabolizing enzymes, has been reported to induce oxidative stress and epigenetic changes, which could alter UGT expression in the brain. Here, we aimed to clarify the effects of PB on Ugt1a6 and Ugt1a7 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
1
13
1
Order By: Relevance
“…25) Following PB treatment, Ugt1a6 mRNA was induced 3.0-and 2.9-fold in the striatum and thalamus, respectively. 33) These results are inconsistent with the hypothesis mentioned above that Ugt1a6 and Ugt1a7 are involved in this glucuronidation. In addition, β-estradiol 3-glucuronidation was not correlated with serotonin (r=−0.18) or APAP (r=0.01) glucuronidation among the eight brain regions.…”
Section: )contrasting
confidence: 57%
See 1 more Smart Citation
“…25) Following PB treatment, Ugt1a6 mRNA was induced 3.0-and 2.9-fold in the striatum and thalamus, respectively. 33) These results are inconsistent with the hypothesis mentioned above that Ugt1a6 and Ugt1a7 are involved in this glucuronidation. In addition, β-estradiol 3-glucuronidation was not correlated with serotonin (r=−0.18) or APAP (r=0.01) glucuronidation among the eight brain regions.…”
Section: )contrasting
confidence: 57%
“…Ugt1a6 and Ugt1a7 mRNAs in the rat brain have been reported to be induced by treatment with BNF 25) and PB 33) at the same dosages as those in the present study. If β-estradiol 3-glucuronidation is catalyzed mainly by Ugt1a6 and Ugt1a7, this glucuronidation will be increased by the Ugt inducers in vivo.…”
Section: )supporting
confidence: 51%
“… or Sakakibara et al . . PCR amplification conditions were as follows: initial 10 s at 95 °C; 40 cycles of 5 s at 95 °C and 30 s at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, UGT1A may be involved in local drug metabolism in the brain. It was previously reported that Ugt1a in the rat brain was increased by treatment with typical Ugt inducers, such as β‐naphthoflavone (Sakakibara, Katoh, Kondo, & Nadai, ) and phenobarbital (Sakakibara, Katoh, Kondo, & Nadai, ), indicating that changes in UGT1A expression could affect the efficacy of a central‐acting drug by altering its concentration in the brain.…”
Section: Introductionmentioning
confidence: 99%